Weight Monitoring Waste Bin Based on Internet of Things (IOT) - Ahmad, Nor Akmal; Zohari, Mohd Hakimi (Progress in Engineering Application and Technology, 2020)
At present, one of the challenges in most cities are cleanness of the environment regarding the garbage management. In order to avoid overload of the garbage and improve the cleanliness, Weight Monitoring Waste Bin Based on IOT is designed. In the proposed system, the weight of the garbage is detected with the help of weight sensor HX711 and sent to the user for garbage collection through Blynk Application. Ultrasonic sensor is used to detect the people coming closely to the garbage bin with trash while the bin is at full status and block adding of any more garbage to the bin by notification. The peripheral sensors used are interfaced through the Arduino microcontroller. Moreover, LED will change the colour with three condition where red, green and orange. This will capably help to monitor the garbage collection to make the environment smart, clean and safe.